¬¬The socio-economic profile of hikers in the mountains of Valencia Region, Spain: a comparative study between the perceptions of hikers' accommodation entrepreneurs and the hikers’ profile - Antonio Vidal-Matzanke; Jorge Terrades-Daroqui; Pablo Vidal-González (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The main objective of this study is to compare the perceptions of the socioeconomic profile that tourism operators have about their hikers/visitors with the socioeconomic profile of hiking users in the mountains of Valencia region (Spain).  A mixed methodology has been used. First, 15 semi-structured interviews were conducted with entrepreneurs in the tourism industry. Secondly, 154 surveys were carried out with hikers to characterize their profile. Both samples were cross-checked to see the similarities and differences between the perceptions of both groups. The results indicate that changes in consumer trends, with the emergence of new market niches that are very interesting from a tourism point of view, such as the public new and very interesting market niches from a tourism point of view, such as women and senior female and senior public, as well as the local tourist or one-day hikers. These market segments represent an opportunity to consolidate an increasingly growing market.an increasingly growing market. The results indicate that there are some similarities between some of the demographic and economic variables studied. However, in other variables there is a misperception of practitioners by employers. This information can help to better target potential tourists. This study also provides a very detailed description of specific profiles of hikers. This information can be very useful both for private sports tourism companies to be able to segment their clients and launch very specific promotional strategies.